Representations of women in female-authored anglophone Uchronias: female agency in alternative worlds - Cuervo, Cristian Camilo (ELCH, 2025)
Uchronias, or alternate histories, are a literary genre that enables us to explore the past, play with it, and even transcend it. These narratives speculate on what might have been, but never was, imagining alternative versions to our historiographical reality, and often confronting us with the implications of such scenarios. Despite its undeniable aesthetic and social potential, this genre is commonly overlooked by scholarly studies, particularly with regard to female-authored novels.
Literaturverzeichnis: Seiten 163-196
Keywords: Hochschulschrift; Alternativgeschichte; Frau; Walton, Jo / My real children; Mayhew, Julie / The big lie; Gerber, Robin / Eleanor vs. Ike